MiR155 modulates vascular calcification by regulating Akt‐FOXO3a signalling and apoptosis in vascular smooth muscle cells. Issue 1 (18th November 2020) - Li, Yong; Sun, Wei; Saaoud, Fatma; Wang, Yuzhen; Wang, Quanyi; Hodge, Johnie; Hui, Yvonne; Yin, Sophia; Lessner, Susan M.; Kong, Xiangqing; Fan, Daping
Abstract: microRNA‐155 (miR155) is pro‐atherogenic; however, its role in vascular calcification is unknown. In this study, we aim to examine whether miR155 regulates vascular calcification and to understand the underlying mechanism. Quantitative real‐time PCR showed that miR155 is highly expressed in human calcific carotid tissue and positively correlated with the expression of osteogenic genes. Wound‐healing assay and TUNEL staining showed deletion of miR155 inhibited vascular smooth muscle cell (VSMC) migration and apoptosis. miR155 deficiency attenuated calcification of cultured mouse VSMCs and aortic rings induced by calcification medium, whereas miR155 overexpression promoted VSMC calcification. Compared with wild‐type mice, miR155 −/− mice showed significant resistance to vitamin D3 induced vascular calcification. Protein analysis showed that miR155 deficiency alleviated the reduction of Rictor, increased phosphorylation of Akt at S473 and accelerated phosphorylation and degradation of FOXO3a in cultured VSMCs and in the aortas of vitamin D3‐treated mice. A PI3K inhibitor that suppresses Akt phosphorylation increased, whereas a pan‐caspase inhibitor that suppresses apoptosis reduced VSMC calcification; and both inhibitors diminished the protective effects of miR155 deficiency on VSMC calcification. In conclusion, miR155 deficiency attenuates vascular calcification by increasing Akt phosphorylation and FOXO3a degradation, and thus reducing VSMC apoptosis induced by calcification medium.